A High-Throughput Screening-Compatible Strategy for the Identification of Inositol Pyrophosphate Kinase Inhibitors - Baughman, Brandi M.; Wang, Huanchen; An, Yi; Kireev, Dmitri; Stashko, Michael A.; Jessen, Henning J.; Pearce, Kenneth H.; Frye, Stephen V.; Shears, Stephen B. (PLOS ONE, 2016)
Pharmacological tools—‘chemical probes’—that intervene in cell signaling cascades are important for complementing genetically-based experimental approaches. Probe development frequently begins with a high-throughput screen (HTS) of a chemical library. Herein, we describe the design, validation, and implementation of the first HTS-compatible strategy against any inositol phosphate kinase. Our target enzyme, PPIP5K, synthesizes ‘high-energy’ inositol pyrophosphates (PP-InsPs), which regulate cell function at the interface between cellular energy metabolism and signal transduction. We optimized a time-resolved, fluorescence resonance energy transfer ADP-assay to record PPIP5K-catalyzed, ATP-driven phosphorylation of 5-InsP7 to 1,5-InsP8 in 384-well format (Z’ = 0.82 ± 0.06). We screened a library of 4745 compounds, all anticipated to be membrane-permeant, which are known—or conjectured based on their structures—to target the nucleotide binding site of protein kinases. At a screening concentration of 13 μM, fifteen compounds inhibited PPIP5K >50%. The potency of nine of these hits was confirmed by dose-response analyses. Three of these molecules were selected from different structural clusters for analysis of binding to PPIP5K, using isothermal calorimetry. Acceptable thermograms were obtained for two compounds, UNC10112646 (Kd = 7.30 ± 0.03 μM) and UNC10225498 (Kd = 1.37 ± 0.03 μM). These Kd values lie within the 1–10 μM range generally recognized as suitable for further probe development. In silico docking data rationalizes the difference in affinities. HPLC analysis confirmed that UNC10225498 and UNC10112646 directly inhibit PPIP5K-catalyzed phosphorylation of 5-InsP7 to 1,5-InsP8; kinetic experiments showed inhibition to be competitive with ATP. No other biological activity has previously been ascribed to either UNC10225498 or UNC10112646; moreover, at 10 μM, neither compound inhibits IP6K2, a structurally-unrelated PP-InsP kinase. Our screening strategy may be generally applicable to inhibitor discovery campaigns for other inositol phosphate kinases.